An archaeologist of images: a conversation with Edouard Duval-Carrié and Anthony Bogues. Issue 3 (2nd September 2021) - Gomes Coelho, Rui; Hamilakis, Yannis
Abstract : In the autumn of 2019, Brown University hosted a major exhibition by the world renowned Haitian, Miami-based artist Edouard Duval-Carrié (b. 1954), curated by Brown's Professor of Humanities and Africana Studies, specialist on Haitian history and art, Anthony Bogues. The title was 'The Art of Embedded Histories'. As the title of the exhibition indicates, and as even a cursory look at this work could show, Duval-Carrié's practice and output speak to material and visual culture specialists, and to anthropologists and archaeologists of art, as well as to art historians and scholars of postcolonialism. In this conversation, we engage with both the artist and the curator. Edouard Duval-Carrié deserves to be known more widely amongst material culture specialists, and we hope that the fascinating dialogue that follows will contribute to this.